Analysis of the Quality of Public Services in the Health Sector at Centro Da Saude Vera-Cruz, Municipiu Dili, East Timor - Inácio Sarmento Viegas; Desideius Priyo Sudibyo; Rino Ardhian Nugroho (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to assess user satisfaction and identify areas for improvement in the quality of health services at Centro da Saude Vera-Cruz, Municipio Dili, Timor-Leste. Specifically, it evaluates key service dimensions including tangibility, reliability, responsiveness, assurance, and empathy from the perspective of service users. A quantitative approach was employed, utilizing a Likert scale to measure respondents' perceptions across these dimensions. The data were analyzed using frequency distribution and cross-tabulation based on respondent characteristics such as age and marital status. The results indicate that most respondents expressed agreement, strong agreement, and high satisfaction with the health services provided, although a minority expressed dissatisfaction. Further analysis showed that respondents aged 31-40 were more likely to express strong agreement with service quality. Overall, among the 60 respondents surveyed, the findings reflect a generally positive perception of the health services at Centro da Saude Vera-Cruz, while highlighting certain aspects where dissatisfaction remains. These insights offer a foundation for targeted improvements in service delivery.